Implementation of Brain-Based Learning Web-Assisted to Improve Students Mathematical Reasoning - Dewi, Nuriana Rahmani; Kusumah, Yaya Sukjaya (Unnes Journal of Mathematics Education, 2017)
Tujuan penelitian ini adalah untuk menganalisis secara komprehensif peningkatan kemampuan penalaran matematis mahasiswa sebagai akibat dari penerapan Brain-Based Learning Berbantuan Web dan pembelajaran konvensional. Metode penelitian yang digunakan adalah metode campuran (mixed method) dengan concurrent embedded design sebagai desain penelitian. Populasi dalam penelitian ini adalah seluruh mahasiswa Jurusan Matematika salah satu perguruan tinggi di Semarang Jawa Tengah, sedangkan sampelnya adalah para mahasiswa yang sedang menempuh Mata Kuliah Kalkulus Integral, baik yang berasal dari Program Studi Matematika maupun Program Studi Pendidikan Matematika. Sampel diambil dari masing-masing program studi secara acak sehingga didapatkan dua kelompok, satu kelompok eksperimen yang mendapatkan Brain-Based Learning Berbantuan Web dan satu kelompok yang mendapatkan pembelajaran konvensional. Kesimpulan yang didapat dari penelitian ini adalah peningkatan kemampuan penalaran matematis mahasiswa yang mendapatkan Brain-Based Learning Berbantuan Web lebih baik daripada mahasiswa yang mendapatkan pembelajaran konvensional. The main purpose of this research is to analyze comprehensively the enhancement of the students’ mathematical reasoning as the result of the implementation of web-assisted brain-based learning and conventional learning. This research used mixed method by combining quantitative and qualitative methods under concurrent embedded design. The population of this research consisted of all students in the mathematics department of one of universities in Central Java. The sample was groups of students in the Study Program of Mathematics and Mathematics Education who enrolled in Integral Calculus course. From these two study programs, two sample groups (experiment group and control group) were selected randomly. An experiment group was taught by using web-assisted brain-based learning, while the other group (control group) was taught by using conventional learning. From this research, it can be concluded that the enhancement of the students’ mathematical reasoning who were taught by using web-assisted brain-based learning are better than the achievement and enhancement of those who were taught by using conventional learning.